Viabilidade da estimulação elétrica nervosa transcutânea e efeitos do exercício físico na variabilidade da frequência cardíaca e na capacidade funcional de indivíduos com doença arterial periférica - Ana Paula Ferreira (2020)
Peripheral arterial disease (PAD) is due to stenosis of the peripheral arteries, especially the lower extremities. The clinical condition of individuals with PAD can vary from asymptomatic to the presence of limiting symptoms such as intermittent claudication, which occurs when the oxygen supply is insufficient to satisfy the metabolic requirements of the skeletal muscle in activity. Despite the clear benefits of exercise therapy, more than 45% of individuals with PAD do not adhere to the recommendations of health professionals for regular exercise due to the symptom of intermittent claudication. Thus, strengthening strategies that minimize the limping symptom in order to increase the walking distance, in this group of individuals, is clinically relevant, since the greater the walking distance, the better the impact reported on the quality of walking. life and functional capacity. Thus, a therapeutic option that has been gaining prominence in vascular rehabilitation is non-invasive transcutaneous electrical nerve stimulation (TENS). Although studies on the effects of TENS on claudication of vascular origin are still incipient, the potential mechanisms that may explain a functional improvement in this group of individuals may be related to a greater supply of oxygen through collateral circulation and vasodilation, in addition to a reduction in pain, that involves different mechanisms. Based on the above, the objectives of the thesis were: a) to describe the feasibility, the barriers during the recruitment and intervention period, the level of participation and adherence of a randomized clinical trial, to verify the effects of TENS, associated with the training of walking in functional capacity, cardiorespiratory fitness and cardiovascular autonomic modulation in individuals with PAD and intermittent claudication; b) verify the effect of 12 weeks of supervised aerobic training on cardiac autonomic modulation and functional capacity of individuals with PAD. For this, two studies were developed. In the first study, 63 participants were selected, of which 12.6% were included. Eight individuals with PAD and intermittent claudication underwent an experimental protocol that lasted eight weeks. Participants were submitted to tests to assess cardiac autonomic modulation through heart rate variability (HRV) and 4-second test; tests to assess functional capacity through incremental shuttle walking test (ISWT) and test on a treadmill with constant speed associating expired gas analysis and to Walking Impairment Questionnaire (WIQ) at the beginning and end of treatment. The experimental group received 45 minutes of TENS 10 Hz, followed by 30 minutes of aerobic exercise, of the walking type and the control group received a TENS placebo also followed by 30 minutes of walking. Descriptive statistics (mean ± standard deviation) and absolute and relative frequencies were used to summarize the characteristics of the participants, initial recruitment data and pre and post protocol outcome measures. Regarding recruitment, the discoveries of the present study showed that the most efficient sources were: i) referral by a doctor and ii) referral by a physiotherapist. With regard to barriers, participants were excluded for the following reasons: failure to meet the criteria (41/65%), impaired mobility (6 / 9.5%), transportation (5 / 7.9%), release from work (1 / 1.6%) and lack of interest (2 / 3.2%). After screening, only 12.6% (8 of 63 participants) were included in the clinical trial and the overall participation was 99 / 51.6% in a total of 192 sessions offered. Finally, it was not possible to achieve success in recruitment and membership rates. The results of this study reinforce that PAD is neglected and that strategies that include a multidisciplinary approach with effective participation of nursing, physiotherapy, medicine and nutrition professionals are necessary to optimize the care for individuals with PAD. In the second study, 12 participants were selected with a diagnosis of PAD and intermittent claudication, of both sexes, with ankle-arm rest index <0.9, without pain at rest. They performed 12 weeks of supervised aerobic training of the walking type, three times a week, with intensity until the limiting symptom. The evaluation of cardiac autonomic modulation (CAM) included the linear and non-linear analysis of HRV. Functional capacity was assessed using the ISWT. Paired t and Wilcoxon tests were performed to compare the pre and post evaluation moments. The correlation between clinical variables with variance change deltas and high frequency (HF) power were performed using Spearman's correlation. The level of significance adopted was 5%. In comparison to the values before the intervention, the variance and the PA band increased (p <0.01). The total walking distance at ISWT also increased (0,004). There was a moderate inverse correlation between the level of obstruction and the vasovagal response (rho = -0.56; p = 0,001). Thus, it was possible to conclude that there was an increase in parasympathetic modulation and an improvement in functional capacity after 12 weeks of training. Finally, the realizations achieved by study 1, evidenced the need to strengthen multidisciplinary strategies for the proper management of individuals with PAD. Study 2, while being a pilot study, showed that regular exercise can improve the sympathetic-vagal balance of these patients.